Osimertinib for Patients With EGFR-Mutated Non-Small Cell Lung Cancer: Current Evidence. - Tang, Xiumei; Chen, Yanmei; Zhu, Yuan; Liu, Yuan; Li, Weimin; Wang, Wenzhao; Wang, Zhoufeng (Clinical Medicine Insights: Oncology, 2026)
Background: Osimertinib, a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, has demonstrated efficacy across multiple treatment lines for patients with EGFR-mutated non-small cell lung cancer (NSCLC). However, the optimal treatment sequence and comparative effectiveness vs alternative therapies remain unclear. Methods: A systematic review and meta-analysis was conducted following the PRISMA 2020 guidelines. Embase, Medline (via Ovid), PubMed, Cochrane Central Register of Controlled Trials, Web of Science, and Google Scholar were searched from inception to May 31, 2025. Clinical trials comparing osimertinib with other treatments (placebo, EGFR-tyrosine kinase inhibitors [TKIs], chemotherapy, targeted therapy) in patients with EGFR-mutated NSCLC were included. Primary outcomes included objective response rate (ORR), median progression-free survival (mPFS), disease control rate (DCR), overall survival (OS), and adverse events. Subgroup analyses were performed by treatment line and comparator type. Risk of bias was assessed using the Cochrane RoB 2 tool. Statistical analysis was performed using R version 4.5.0 with random-effects models for high heterogeneity (I2> 50%). Results: Sixteen studies encompassing 4931 patients were included. Osimertinib demonstrated significantly superior ORR compared to control treatments (relative risk [RR] = 1.59, 95% confidence interval [CI] = 1.16 to 2.17, P <.001), exceeding the minimal clinically important difference threshold. The mPFS benefit was substantial (standardized mean difference [SMD] = 4.53 months, 95% CI = 1.23 to 7.82, P <.0001), with greater improvements observed in first-line therapy (SMD = 3.25, 95% CI = 0.52 to 5.97) vs second-line treatment (SMD = 7.61, 95% CI = −10.08 to 25.30). The DCR was significantly improved (RR = 1.26, 95% CI = 1.05 to 1.52, P <.0001). The OS showed modest but consistent improvement (SMD = 0.18, 95% CI = 0.11 to 0.26, P <.0001) with no heterogeneity (I2= 0%). Osimertinib was most effective vs chemotherapy and showed consistent benefits vs first-generation TKIs. Adverse events included increased upper respiratory tract infections, skin toxicities, and QT prolongation, while nausea and alopecia were reduced. Conclusions: Osimertinib demonstrates superior efficacy across multiple endpoints in patients with EGFR-mutated NSCLC, with benefits observed in both first-line and second-line settings. The treatment provides clinically meaningful benefits with a manageable safety profile, supporting its use as a preferred therapeutic option across different treatment sequences.